The Arts and Culture Industry’s Contribution To The Economy and Its Situation During the Pandemic - Bozena FRACZEK (Communications of International Proceedings, 2021)
The contribution of the arts and culture sectors to the economy is not often examined. Meanwhile, the sector occupies a surprisingly high position among the most important areas for the economy in terms of GDP share. It is often ahead of other sectors of the economy in individual countries. The time of the pandemic has proved to be particularly difficult for this industry. The situation of the arts and culture industry during the pandemic is full of paradoxes. Although the industry has occupied a significant place in the economy (share in GDP) for a long time, the government’s support in response to the pandemic lockdown is very limited and at times problematic. On the one hand, the pandemic has resulted in an intensification of demand for cultural and creative content throughout the lockdown period. On the other hand, economic indicators predict that after the lockdown, the sector will both be one of the most affected, for which recovery will probably be one of the most difficult and slowest. The coronavirus pandemic has also affected changes in traditional patterns of consumption of arts and culture. The conditions in which the arts and culture industry has found itself indicate enormous changes in the sector, which will also continue after the opening of economies and individual industries. The aim of the paper is to present the role of the arts and culture industry in economies using the example of selected countries, as well as to analyze the situation this sector find itself in after the lockdown caused by the COVID-19 coronavirus pandemic. The research consists of document analysis, a form of qualitative research using analysis of documentary evidence.
Keywords: Art and Culture Industry; Pandemic; Economy